2001
DOI: 10.4141/s00-059
|View full text |Cite
|
Sign up to set email alerts
|

Wheat yield and grain protein variation within an undulating soil landscape

Abstract: Wheat yield and grain protein variation within an undulating soil landscape. Can. J. Soil Sci. 81: 459-467. The objective of this study was to compare landform element complexes (LEC) and soil series as discrete management units for variable rate N fertilizer application. Crop response attributes including grain yield, and grain protein concentration were studied in ten intensively sampled transects in an undulating glacial till soil-landscape near Miniota, Manitoba. In 1997, a year with growing season precipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…Crop productivity and N uptake can vary with positions within a landscape, particularly on the rolling plains and hummocky landforms of prairie landscapes (Fiez et al 1994(Fiez et al , 1995Walley et al 2001). Manning et al (2001b) found that, for a growing season with precipitation 62% higher than average, wheat yield and N uptake were significantly less at lower slope than at upper slope positions when N fertilizer was applied at 45 and 90 kg N ha -1 . However, the opposite trend in wheat yield was observed in another year with growing season precipitation 37% below average.…”
mentioning
confidence: 99%
“…Crop productivity and N uptake can vary with positions within a landscape, particularly on the rolling plains and hummocky landforms of prairie landscapes (Fiez et al 1994(Fiez et al , 1995Walley et al 2001). Manning et al (2001b) found that, for a growing season with precipitation 62% higher than average, wheat yield and N uptake were significantly less at lower slope than at upper slope positions when N fertilizer was applied at 45 and 90 kg N ha -1 . However, the opposite trend in wheat yield was observed in another year with growing season precipitation 37% below average.…”
mentioning
confidence: 99%
“…Fiez et al (1994) observed the highest grain protein at shoulder positions, whereas the lowest was observed at north exposed backslope positions. Manning et al (2001) observed the lowest protein content for wheat at F positions and attributed that to the greater biomass production at that landform together with a dilution effect. One possible explanation of such a difference between results at our field site and the literature might be differences in the availability of soil nitrogen to the plants (Jowkin and Schoenau, 1998), or attributed to late season moisture stress (Fiez et al, 1994).…”
Section: Analysis Of Internode and Spike Length Across Landformsmentioning
confidence: 90%
“…If data showed no normal distributions, the Kruskal-Wallis test was applied. Generally an a=0.2 was used (Manning et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Mean grain protein concentrations were significantly different with respect to slope position and increased from the lower to the upper slope position at each site (Table 6). Manning et al (2001b) also found that grain protein concentration increased upslope and suggested it was likely due to proportionally less yield produced. An upper slope position would be expected to have relatively lower levels of plant available water, which may cause lower total grain and protein yields.…”
Section: Grain Protein Concentrationmentioning
confidence: 92%
“…This increased biomass production has in turn resulted in greater SOC content, which contributes to a greater available water content in the soil, potentially mineralizable N, and soil profile development. Lower yields and available moisture on the upper slope position generally result in higher grain protein concentrations in winter wheat (Mulla et al 1992;Manning et al 2001b). Thus, the use of topography to aid in the delineation of N management units is appealing as it would identify some of the more significant changes in soil characteristics in a field, as well as being a method of delineation to which producers can readily relate from a crop production viewpoint.…”
mentioning
confidence: 99%